Nitrogen fertilizer use reduction by two endophytic diazotrophic bacteria for soil nutrients and corn yield - Nguyen Van Chuong; Trang Nguyen Ngoc Phuong; Thuan Nguyen Van (Communications in Science and Technology)
Today, the utilization of endophytic diazotrophic bacteria (EDB) purposely to minimize the application of urea fertilizer (UF), and enhance soil fertility, crop quality and corn yield in sustainable agricultural practices is an inevitable trend. The experiment was arranged outside the AGU green house of Agriculture Research Center, An Giang university, Vietnam, which consisted of two factors: (i) two EDB species [Bacillus sp.  NTLG2-20 (Bacillus A) and Bacillus arybhattai strain CM44 (Bacillus B)] and (ii) three UF ratios (0.0, 100 and 200 kg N ha-1) and four replications. Research data presented that the fresh cob yield of Bacillus A was found 4.0% higher than that of Bacillus B and 12.7% than that of non EDB inoculation. Furthermore, the inoculation of Bacillus B had 9.02% higher fresh cob yield compared to non-inoculation. The 50% reduction of UF application combined EDB addition obtained the fresh cob with no significant difference, compared to 100% recommended urea application. The interaction between the effectiveness of EDB inoculation and UF reduction was clearly different in favor of corn grown on sandy loam soils with low nutrient contents. Both Bacillus A and Bacillus B had the abilities of high yield and good nitrogen fixation with the potential to simultaneously improve soil fertility and corn yield. The results of this study demonstrated that two strains of Bacillus A and Bacillus B have the potential to promote the growth and increase the yield of peanuts, and it should be suggested for future biological fertilizer production.